Analisis Lingkungan Kerja Fisik Pada Pekerja Produksi Untuk Menentukan Penjadwalan Istirahat Pada Pekerja - Maulana Hanif Azhar; Fitria Aulia; Mauza Nandika; Mirza Rahmat Hak; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2024)
Physical workings and physiological data of the work operator on the work of human at work. Therefore, it is necessary to design the working environment for operator comfort and work time determinant. The research process by measuring the physical work environment, the operator's physiological data, the determination of time and work break time. The transmitter and the frais are too dark, the temperature is too hot and humid, it is necessary to increase the number of lamps and air ventilation around the lathe and frais operators. Frais machine operators generated CVL of 26.7% which is still below 30% then operators of frais machines can not be exposed to work. Lathe operators of CVL results are 31.34%, because the results are in the range of 30% - 60% then the lathe operators experience work that result to operator performance. Lathe operators require a break time of 20.85 minutes and the engine operator frais 18.85 minutes.